How Does Industrialization Affect the Structure of International Trade? : The Japanese Experience in the Pacific Basin, 1975-85 - Shirai, Sayuri (IMF Working Papers; Working Paper ;, 1994)
This paper provides a theoretical model to address the issue of how industrialization affects the structure of international trade. Considering both horizontal and vertical product differentiation, the model shows that intra-industry trade increases when product quality improvement emerges in a developing country and when a difference in relative factor endowments between a developed and a developing countries shrinks. To promote understanding of the conclusions of the model, the paper also uses actual trade data between Japan and Indonesia and between Japan and Korea.